Extraction and characterization of chitosan from shrimp shell waste using two different sequence method - Wylericayenny Lian @ William (2020)
Crustacean species such as shrimps are global production that has been reported to generate tons of waste annually that could affect the environment in terms of odour and aesthetic damage. Chitin can be derived into chitosan through deacetylation. Chitosan offers more potential in industrial application compares to chitin. However, poor quality of chitosan has restricted its potential in application due to the difficulties in maintaining its solubility, degree of deacetylation (DDA), ash and moisture content of chitosan. Therefore, the main focus of this study was to extract chitin and chitosan from shrimp shell waste using different sequence of chemical extraction and compare the yield and the physicochemical characteristics of chitosan produced from respective processes (Deproteination-Demineralization, DemineralizationDeproteination). In Pl, deproteination occurred in the first step and followed by demineralization and deacetylation. While P2 was started with demineralization step and followed by deproteination and deacetylation. The results showed that the percentage yield of chitosan was higher for P2 with 22.23% compared to Pl. In spite of that, the quality of P2 chitosan was low in terms of DDA, solubility and ash content, which were 76.47%, 37.79% and 2.67%, respectively. In contrary, when deproteination was carried out before demineralization (Pl), the DOA of chitosan, solubility and ash content were improved to 91.26%, 100% and 0.24%, respectively.